Timor-Leste : Report on Observance of Standards and Codes (ROSC)-Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2010)
Timor-Leste is a unitary state and has made significant progress with improving its fiscal transparency. The government has adopted a transparent, fiscally sustainable governance framework for the petroleum sector. Nonetheless, there are still many areas in which Timor-Leste diverges from the International Monetary Fund Code for clarity of roles and responsibilities, openness of the budget process, public availability of information, and guarantees of integrity. Particular attention should be paid to improvement of the systems consolidating fiscal information and enabling fiduciary responsibilities of the Ministry of Finance.